Parenting style and creative potential of children - Dechaume, Merav; Lubart, Todd (Educar em Revista, 2021)
These days, individuals must be able to think and produce creatively. Therefore, stimulating creative abilities forms an important objective for educators and professionals. Parenting style that includes daily child-rearing practices, creativity specific parent-child interactions, and perceptions about creativity relates fundamentally to the development of creative potential. These constructs shape children’s understanding of their environment enabling them to form a mindset, personal qualities, traits and skills that help determine attitudes towards creativity. This preliminary study explored the relationship between parenting style and children’s creative potential. Participating parents responded to questionnaires assessing the level of rigidity structure in daily child rearing practices, creativity specific parentchild interactions, and parental perceptions of their children’s creative self-efficacy. Their children completed the Evaluation of Creative Potential (EPoC) instrument that measures convergent and divergent thinking in graphic and verbal domains. Although, we found no statistically significant relationship between parenting style and creative potential, several parentchild interactions correlated significantly with parental perceptions. The more parents encourage novelty, the more they perceive their children to show creative behavior. Additionally, too much support for direct creativity could diminish certain creativity - related behaviors such as fantasizing. These findings support the notion that parental attitudes and interactive behaviors are significant predictors of children’s creative abilities, thus suggesting possible avenues for further research and educational practices to support novel, discovery activities.